A partial cooperative control vehicle‐to‐vehicle trajectory planning algorithm with potential field constraints of arc‐shaped road's boundary and vehicles' relative position. Issue 11 (2nd July 2022) - Zhang, Kuoran; Wang, Jinxiang; Yan, Yongjun; Chen, Nan; Yin, Guodong
Abstract: In this paper, a vehicle‐to‐vehicle (V2V) trajectory planning algorithm for two vehicles driving in an arc‐shaped road is represented, in which the characteristics of human drivers are taken into consideration. Safety constraints including vehicle stability, road boundaries, and vehicles collision avoidance are considered. The boundary constraint of the arc‐shaped road is realized with a potential field method. The potential field method is also employed to realize the vehicles collision avoidance constraint and vehicle distance margin. The concept of partial cooperative control is presented, which can depict the collaboration of the vehicles more accurately. The algorithm is designed with a partial cooperative control pattern, employing model predictive control (MPC). The effectiveness of the algorithm is verified by software simulation in a scenario of overtaking in arc‐shaped roads. The algorithm can accomplish the V2V collaboration trajectory planning task successfully. The performance of the algorithm representing different collaboration degrees and phases grouping in complex scenarios is also studied.